Secretarial procedures and administration - Hanna, J.Marshall; Popham, Estelle L.; Beamer, Esther Kihn. (Cincinnati : South Western Publishing Company, 1968)
The book contains guidelines in Secretarial Procedures and Administration. It covers 9 major topics include: the secretarial profession; secretarial typewriting and duplicating; the secretary's communication responsibilities; secretarial use of transmittal services; secretarial management of records; among others.
"Formerly effective secretarial practice".
Includes bibliographical references and index.
uaa 24/01/2019
Loans
Keywords: Office practice